Utilizing Load Cell Sensor Technology for the Hanging Scales as a Detector of Infusion Fluids Volume as a Prevention to Embolism in Patients - Sumanto, Budi; Bagaswara, Dicky; P., M. Ma'ruf Rizky SP; Akbar, M. Amirul; P., Debora Naomi S; Afifah, Hanny (2016)
Infusion as one of vital factors which is used to support health has become an integral component for health care providers. In addition to the infusion mostly used by patients, health care providers, such as hospitals, have to work effectively to optimize the distribution of it to the patient. However, the number of infusion must be distributed to all the patients in turn are not comparable with the capabilities and the number of medical personnel to effectively distribute. The impact to this is that many patients who is hospitalized will be suffering from emboli, the worst case is failing of vital organs function and death. This paper will describe the explanation of the creation of hanging scales named Nurse Warning Notification (WARNET) which can detect the volume of IV fluids and give a signal to the patient and the nurse when the bag is almost empty. This tool uses three essential components, namely load cell as the pressure sensors, HX711 which acts as stress risers for the load cell, as well as the Arduino Uno as intermediaries to apply the program. The three main components are assembled into a hanging scales to which infusion fluid can be hung and later will forward a signal which can be heard and seen by the patient and of course the nurse. In brief, WARNET can act as an important factor in reducing the likelihood of embolism in patients and increase the effectiveness of the performance of nurses in a health-care provider.